Image quality improvements in C-Arm CT (CACT) for liver oncology applications: Preliminary study in rabbits. Issue 5 (September 2013) - Tacher, Vania; Bhagat, Nikhil; P. Rao, Pramod; Lin, MingDe; SchÄfer, Dirk; Noordhoek, Niels; Eshuis, Peter; Radaelli, Alessandro; Liapi, Eleni; Grass, Michael; Geschwind, Jean-François
Abstract: Introduction : C-Arm CT (CACT) is a new imaging modality in liver oncology therapy that allows for the acquisition of 3D images intra-procedurally. CACT has been used to enhance intra-arterial therapies for the liver by improving lesion detection, avoiding non-target embolization, and allowing for more selective delivery of agents. However, one of the limitations of this technology is image artifacts created by respiratory motion.Purpose: To determine in this preliminary study improvements in image acquisition, motion compensation, and high resolution 3D reconstruction that can improve CACT image quality (IQ).Material and methods : Three adult male New Zealand white rabbits were used for this study. First, a control rabbit was used to select the best x-ray acquisition imaging protocol and then two rabbits were implanted with liver tumor to further develop 3D image reconstruction and motion compensation algorithms.Results : The best IQ was obtained using the low 80 kVp protocol with motion compensated reconstruction with high resolution and fast acquisition speed (60 fps, 5 s/scan, and 312 images).Conclusion : IQ improved by: (1) decreasing acquisition time, (2) applying motion-compensated reconstruction, and (3) high resolution 3D reconstruction. The findings of this study can be applied to future animal studies and eventually could be translated into the clinical environment.